Inventing the Electronic Century : The Epic Story of the Consumer Electronics and Computer Industries, with a New Preface. - Chandler Jr., Alfred D. (Cambridge : Harvard University Press, 2005)
Consumer electronics and computers redefined life and work in the twentieth century. In Inventing the Electronic Century, Pulitzer Prize-winning business historian Alfred D. Chandler, Jr., traces their origins and worldwide development. This masterful analysis is essential reading for every manager and student of technology.
Intro -- Contents -- Title page -- Copyright -- Dedication -- Acknowledgments -- Contents -- Preface to the Paperback Edition -- 1. Introduction: Concepts and Approach -- 2. Consumer Electronics: The United States: The Creation and Destruction of a National Industry -- 3. Consumer Electronics: Japan's Paths to Global Conquest -- 4. Mainframes and Minicomputers: The Computer Industry Created in the United States -- 5. The Microprocessor Revolution: The Computer Industry Recast in the United States -- 6. The National Competitors: Europe's Computer Industries Die, Japan's Industry Challenges -- 7. The Consumer Electronics and Computer Industries as the Electronic Century Begins -- 8. The Significance of the Epic Story -- Appendices -- Notes -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic industries; Computer industry; Competition, International; Electronic books